Evaluating the impact of a tertiary multidisciplinary meeting in metastatic breast cancer: A prospective study - Belinda Sassé; Sammy Shaya; Jessica Nimmo; Katie Cao; Daphne Day; Katie Evans; Catherine Healy; Gwo-Yaw Ho; Gillian Kruss; Amelia McCartney; Linda Mojzisova; Ranjana Srivastava; et al. (Breast)
Background: Metastatic breast cancer (mBC) guidelines recommend multidisciplinary meetings (MDM), but there is limited research on their impact. This prospective study examines the impact of an mBC MDM on management plans, their implementation rate, and costs and benefits at an Australian metropolitan breast cancer center. Methods: Consecutive mBC MDM patients were enrolled. Oncologists recorded their management plans before the MDM. Following the MDM, consensus plan was recorded and compared to the pre-MDM plan. Plans were categorised as no change, low impact, or high impact. High impact was defined as major treatment change or trial referral. Plan implementation was assessed four months post-MDM. Co-primary endpoints were proportion of plans changed pre/post-MDM and the proportion of high vs. low-impact changes. Estimates of time spent on the MDM and time savings were collected. Results: 114 MDM presentations for 95 patients were recorded from October 2023 to July 2024. 65 (57.0 %) presentations resulted in a plan change (p < 0.001); 32 (28.1 %) were high impact (p < 0.001). Follow up data was collected for 77 presentations; 65 (84.4 %) were fully implemented. 42 presentations resulted in high impact recommendations, of which 39 were implemented (92.6 %) (p = 0.005). The MDM earned $571.18/week with estimated costs of $1584.63, a $1013.45 deficit. Costs were likely offset by estimated savings from improved clinic efficiencies. Conclusion: MBC MDMs result in significant, actionable changes to patient management. 28.1 % of presentations resulted in treatment changes, almost all of which were implemented. Costs were offset by improved clinic efficiencies. MBC MDMs enhance care in this diverse patient population.